Fundamentals of Magneto-Optical Spectroscopy - Sato, Katsuaki; Ishibashi, Takayuki (Frontiers in Physics, 2022)
This paper provides a comprehensive review of magneto-optical (MO) spectroscopy. In the first place, different methods of MO measurements such as the Faraday effect, MO Kerr effect, and Cotton-Mouton effect are briefly introduced. Next, macroscopic and microscopic origin in magnetic materials is summarized. In the third part, measuring techniques for MO spectroscopies are reviewed, with a particular reference to the polarization modulation technique.